Investigation of omeprazole and phenacetin first‐pass metabolism in humans using a microscale bioreactor and pharmacokinetic models. (1st April 2015) - Bricks, Thibault; Hamon, Jérémy; Fleury, Marie José; Jellali, Rachid; Merlier, Franck; Herpe, Yves Edouard; Seyer, Alexandre; Regimbeau, Jean‐Marc; Bois, Frédéric; Leclerc, Eric
Abstract A new in vitro microfluidic platform (integrated insert dynamic microfluidic platform, IIDMP) allowing the co‐culture of intestinal Caco‐2 TC7 cells and of human primary hepatocytes was used to test the absorption and first‐pass metabolism of two drugs: phenacetin and omeprazole. The metabolism of these drugs by CYP1A2, CYP2C19 and CYP3A4 was evaluated by the calculation of bioavailabilities and of intrinsic clearances using a pharmacokinetic (PK) model. To demonstrate the usefulness of the device and of the PK model, predictions were compared with in vitro and in vivo results from the literature. Based on the IIDMP experiments, hepatic in vivo clearances of phenacetin and omeprazole in the IIDMP were predicted to be 3.10 ± 0.36 and 1.46 ± 0.25 ml/min/kg body weight, respectively. This appeared lower than the in vivo observed data with values ranging between 11.9–19.6 and 5.8–7.5 ml/min/kg body weight, respectively. Then the calculated hepatic and intestinal clearances led to predicting an oral bioavailability of 0.85 and 0.77 for phenacetin and omeprazole versus 0.92 and 0.78 using separate data from the simple monoculture of Caco‐2 TC7 cells and hepatocytes in Petri dishes. When compared with the in vivo data, the results of oral bioavailability were overestimated (0.37 and 0.71, respectively). The feasibility of co‐culture in a device allowing the integration of intestinal absorption, intestinal metabolism and hepatic metabolism in a single model was demonstrated. Nevertheless, further experiments with other drugs are needed to extend knowledge of the device to predict oral bioavailability and intestinal first‐pass metabolism. Copyright © 2015 John Wiley & Sons, Ltd.